2012
DOI: 10.1007/s00421-012-2416-7
|View full text |Cite
|
Sign up to set email alerts
|

Time-course response in serum markers of bone turnover to a single-bout of electrical stimulation in patients with recent spinal cord injury

Abstract: The objective of the present repeat-measures study was to determine whether plasma serum levels of testosterone, cortisol, osteocalcin or type I collagen C-telopeptide (CT) are acutely affected following an electro-myostimulation (EMS) bout, and their relation to bone mineral density and muscle mass. Ten men with recent (8 weeks) thoracic spinal cord injury (SCI) (ASIA A) and 10 age-matched able-bodied (AB) men performed one EMS bout on the quadriceps femoris muscle. Blood samples were drawn at basal condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…13,14 The intensity of the evoked contraction proved to be an important factor in an electrical stimulation training program in SCI, 27 which is true for patients with either recent 13 or chronic SCI. 28 The present protocol was proved to acutely induce positive alterations in serum markers of bone turnover in persons with recent SCI 24 ; therefore, the selected evoked contraction intensity was thought to be sufficient to elicit positive changes in bone metabolism longitudinally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,14 The intensity of the evoked contraction proved to be an important factor in an electrical stimulation training program in SCI, 27 which is true for patients with either recent 13 or chronic SCI. 28 The present protocol was proved to acutely induce positive alterations in serum markers of bone turnover in persons with recent SCI 24 ; therefore, the selected evoked contraction intensity was thought to be sufficient to elicit positive changes in bone metabolism longitudinally.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of this protocol was based on the positive acute adaptation, which was proved to induce on bone biomarkers in recent spinal cord injured persons. 24 The EMS training program was performed 5 days a week for 14 weeks by the same physiotherapist for a given subject. Sessions took place in the morning or in the afternoon depending on participant's availability.…”
Section: Electrical Stimulation Instrumentation and Training Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Several animal and human studies have shown new bone formation in response to electrical stimulation [7375]. In a small study of 8 men with acute thoracic motor complete SCI, a single session of electrical stimulation reduced c-telopeptide levels indicating reduced bone resorption 48 hours after treatment [76]. Electrical stimulation of the quadriceps muscle in upright stance reduced bone loss and preserved trabecular bone micro-architecture at the distal femur in seven subjects with SCI compared to 5 subjects who stood without stimulation and 15 subjects with SCI who received no standing or stimulation [77].…”
Section: Treatment Of Sci-induced Osteoporosis: Mechanical Loadingmentioning
confidence: 99%